Leakage from medically-certified to self-certified workplace absence among norwegian employees. Issue 1 (1st January 2017) - Karlsen, Geir R.; Ytterstad, Elinor
ABSTRACT: There are two different kinds of sickness absence in Norway: self-certified absence (SCA), and medically-certified absence (MCA). In this study of 6437 Norwegian employees, we applied logistic regression models for a dichotomous SCA variable on initially 38 independent variables including age and gender. Our findings showed that employees reporting long-term health issues but no record of MCA in the past 12 months (9.4% of the employees), had significantly higher odds of SCA than other employees. We claim that this constitutes a leakage of workplace absence from MCA to SCA, since these employees have long-term health issues. In addition, we found that women in this group were more likely to reduce their workload to part-time jobs, compared to other women. We suggest that basing MCA on diagnoses from a certified list contributes to leakage of employees with specific characteristics from MCA to SCA.